1977
DOI: 10.1144/gsl.qjeg.1977.010.03.08
|View full text |Cite
|
Sign up to set email alerts
|

Investigating old dams

Abstract: Summary Examples are given of three dams, two rather old, water impounding dams, the other, more recently constructed, for retaining industrial waste. All three dams suffered some degree of failure and, as a result, were investigated more fully than would otherwise have been the case. At Lluest Wen, following emergency grouting and other work, a detailed examination disclosed so many imperfections in the puddle core that a new slurry trench cut off was provided. A 20 ft diameter shaft at th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1985
1985
2008
2008

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Approx 1 ton/year. (Little, 1977) RATE OF INTERNAL EROSION -PREDICTION AND RISK ASSESSMENT It is suggested that the level of detail which is appropriate to apply to the assessment of vulnerability to rapid internal erosion should be on a risk based approach. This considers whether the Undertaker has reduced risk to as low as reasonably practicable (ALARP), namely whether the measures taken have been proportionate to the reduction in risk that could be achieved.…”
Section: Rate Of Internal Erosion -Experiencementioning
confidence: 99%
“…Approx 1 ton/year. (Little, 1977) RATE OF INTERNAL EROSION -PREDICTION AND RISK ASSESSMENT It is suggested that the level of detail which is appropriate to apply to the assessment of vulnerability to rapid internal erosion should be on a risk based approach. This considers whether the Undertaker has reduced risk to as low as reasonably practicable (ALARP), namely whether the measures taken have been proportionate to the reduction in risk that could be achieved.…”
Section: Rate Of Internal Erosion -Experiencementioning
confidence: 99%